2009
DOI: 10.1111/j.1467-9280.2008.02245.x
|View full text |Cite
|
Sign up to set email alerts
|

Recalling a Witnessed Event Increases Eyewitness Suggestibility

Abstract: People's later memory of an event can be altered by exposure to misinformation about that event. The typical misinformation paradigm, however, does not include a recall test prior to the introduction of misinformation, contrary to what real-life eyewitnesses encounter when they report to a 911 operator or crime-scene officer. Because retrieval is a powerful memory enhancer (the testing effect), recalling a witnessed event prior to receiving misinformation about it should reduce eyewitness suggestibility. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
186
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(201 citation statements)
references
References 33 publications
(41 reference statements)
8
186
7
Order By: Relevance
“…Interestingly, this pattern seems to contradict those reported by Chan et al (2009) Loftus and Greene (1980), in which participants were told that the narrative was written by a professor after he/she watched the video. This suggested that the narrative was based on the professor's memory of the video event.…”
Section: The Testing Effect Verbal Facilitation and Retrieval-enhancontrasting
confidence: 62%
“…Interestingly, this pattern seems to contradict those reported by Chan et al (2009) Loftus and Greene (1980), in which participants were told that the narrative was written by a professor after he/she watched the video. This suggested that the narrative was based on the professor's memory of the video event.…”
Section: The Testing Effect Verbal Facilitation and Retrieval-enhancontrasting
confidence: 62%
“…If retrieval practice enhances memory of a witnessed event, then this enhancement would seem likely to reduce misinformation suggestibility. However, contrary to this possibility, retrieval practice can sometimes increase the negative influence of misleading suggestions on eyewitness memory performance -a finding termed retrieval-enhanced suggestibility (RES, Chan, Thomas, & Bulevich, 2009). Due to the frequency that witnesses engage in repeated retrieval, it is prudent to examine the conditions under which recalling details of a witnessed event might, or might not, produce RES.…”
Section: Retrieval Enhances Eyewitness Suggestibility To Misinformatimentioning
confidence: 99%
“…We do not dwell on the reconsolidation hypothesis in this paper because these experiments were not designed to address this possibility. account ascribes RES to preferential encoding of the misinformation following initial testing (Chan et al, 2009;Thomas, Bulevich, & Chan, 2010). For explication purposes, we refer to this notion as the attention allocation hypothesis (Chan, Wilford, & Hughes, 2012;Thomas et al, 2010).…”
Section: Cognitive Mechanisms Underlying Retrieval-enhanced Suggestibmentioning
confidence: 99%
“…Researchers argue that taking a test strengthens the memory trace for a specific event, which in turn reduces the impact of forgetting and external misinformation (e.g., Chan, Thomas, & Bulevich, 2009). In support of the protective value of testing, studies have frequently found an inoculation effect against misinformation (e.g., Pansky & Tenenboim, 2011; Wang, Paterson, & Kemp, 2014).…”
mentioning
confidence: 99%
“…That is, recent studies have demonstrated elevated false memory rates after taking a test (e.g., Chan & Langley, 2011; Chan & LaPaglia, 2011; Gordon & Thomas, 2014; Wilford, Chan, & Tuhn, 2014). This effect, labeled retrieval‐enhanced suggestibility (Chan et al, 2009), may be related to two underlying mechanisms: a focus on the misinformed items or the overwriting of the original memory trace because of testing. The former mechanism represents a preference for the newly stored (erroneous) information, while the latter causes the previously stored (correct) information to become inaccessible.…”
mentioning
confidence: 99%